Olympic judo champion athletes: motivational aspects of training - Dos Santos, S. L. C.; Emiko Murakami, A. (Revista Multidisciplinar do Nordeste Mineiro, 2025)
The objectives of this work are to identify the motivational factors in Women's Judo athletes train for long term period until they finally become high level in Judo in Brazilian Team. The work employed closed-ended rating values questionnaires Brazilian Olympic Judo team members, (Subject women 20) 41 in total were evaluated. Three professionals` experts of renowned and proven experience in judo competitions validated the questionnaires. The results showed a list of numerous indicators which have been classified and prioritized as: outcome motivation, coping with adversity, peak under pressure, setting goals/mental preparation, concentration, no worries and eager to be trained. All these values were prevalent in the closed-ended questionnaire obtained in this ranking. In conclusion, different factors exist which motivate judo athletes to continue to practice judo without considering the present but the future rewards. On the other hand, their resilience reduces over a long period of time.